Reliability of measures obtained during single and repeated countermovement jumps - Cormack, S. J.; Newton, R. U.; McGuigan, M. R.; Doyle, T. (International Journal of Sports Physiology and Performance, 2008)
To establish the reliability of various measures obtained during single and repeated countermovement jump (CMJ) performance in an elite athlete population. Methods: Two studies, each involving 15 elite Australian Rules Football (ARF) players were conducted where subjects performed two days, separated by one week, of AM and PM trials of either a single (CMJ1) or 5 repeated CMJ (CMJ5). Each trial was conducted on a portable force-plate. The intraday, interday, and overall typical error (TE) and coefficient of variation (CV%) were calculated for numerous variables in each jump type. Results: A number of CMJ1 and CMJ5 variables displayed high intraday, interday, and overall reliability. In the CMJ1 condition, mean force (CV 1.08%) was the most reliable variable. In the CMJ5, flight time and relative mean force displayed the highest repeatability with CV of 1.88% and 1.57% respectively. CMJ1Mean force was the only variable with an overall TE < smallest worthwhile change (SWC). Conclusion: Selected variables obtained during CMJ1 and CMJ5 performance can be used to assess the impact of both acute and chronic training and competition. Variables derived from the CMJ5 may respond differently than their CMJ1 counterparts and should provide insights into differential mechanisms of response and adaptation.